Average mid-term education and the school of Antonio Gramsci - da Silva, Flavia Gonçalves; Bernado, Elisangela da Silva (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2019)
This article presents elements that compose the current debate on the Integral High School in Brazil, more specifically, the public policy entitled Teaching Higher Education Program created in 2009 by the Federal Government and implemented in the different states of the Federation and the school designed by Antonio Gramsci. Seeks through approximations and / or antagonisms to talk with the ideas of this author and others like Frigotto; Motta (2017) and Savianni (2003) who focused on the subject of secondary education in Brazil. The possibility of using Gramsci's concepts in the development of a more egalitarian secondary school was part of the construction of this study. The methodology used was qualitative research, supported by documental analysis and bibliographical research.